THE RELATIONSHIP BETWEEN EXERCISE LOAD AND THE LEVEL OF FATIGUE, ANXIETY, AND AUTONOMIC NERVOUS SYSTEM FUNCTION IN INDIVIDUALS WITH OBESITY, HYPERTENSION, TYPE 2 DIABETES, AND ATHLETES IN THE CONTEXT OF PHYSICAL REHABILITATION - Ataman, Yurii; Oleshko, Tetiana; Shevets, Valentina; Pylypenko, Dmytro; Klymenko, Viktoriia (Eastern Ukrainian Medical Journal, 2025)
Physical activity plays a crucial role in the lives of individuals with type 2 diabetes, hypertension, and obesity, contributing – when maintained within healthy limits – to improved quality and longevity of life. Among athletes, physical activity is fundamental to professional performance, ensuring an adequate level of preparedness for achieving competitive results. Consequently, motivation for engaging in physical exercise varies considerably between populations. The willingness to participate in and regulate physical activity significantly influences its impact on human health. However, the effects of varying levels of training load on the human body remain insufficiently explored. The aim of this study was to examine the relationship between training load and levels of fatigue, anxiety, and autonomic nervous system dysfunction in individuals with obesity, hypertension, type 2 diabetes, and athletes in the context of physical rehabilitation. Materials and Methods. A total of 61 participants were included in the study and divided into two groups: a patient group (9 individuals with type 2 diabetes, hypertension, and obesity) and a group of healthy athletes (52 participants). The physical rehabilitation program for patients included individualized aerobic and strength exercises. In the patient group, the average weekly training duration over the final two weeks was 6.56 ± 2.07 hours, corresponding to a satisfactory level of physical activity (≥ 150 minutes/week). Among athletes, this value was significantly higher, averaging 18.12 ± 4.98 hours per week. Weekly training duration and load volume were assessed. Fatigue was measured using the Fatigue Assessment Scale; well-being (as a component of quality of life) was assessed via the WHO-5 Well-Being Index; insomnia was evaluated using the Athens Insomnia Scale; daytime sleepiness using the Epworth Sleepiness Scale; and anxiety levels were determined using the Hospital Anxiety and Depression Scale. Results. Physical activity had differing effects on the well-being and quality of life of both patients and athletes. If for the former it was a factor in reducing fatigue and improving well-being, then for athletes it was accompanied by a deterioration in psychophysiological indicators. The latter gives grounds to assume that in people with the most significant training load during the week, a decrease in the feeling of well-being may develop precisely as a result of overfatigue, which can be physical and mental-emotional. A similar picture was observed when studying the autonomic nervous system - with an increase in the volume and duration of the load, almost all indicators of heart rate variability improved, while in athletes such a pattern was not established. This is explained by the motivation of athletes to engage in such intensive training that can exceed the level of optimal adaptive capacity of the body, become excessive and be accompanied by the accumulation of fatigue and overtraining. Conclusions. Thus, the findings indicate that the duration and volume of physical activity have a specific impact on well-being and autonomic regulation, varying according to the characteristics of the population studied. In individuals with type 2 diabetes, arterial hypertension, and obesity, training load duration and volume demonstrated an inverse relationship with subjective fatigue and a direct relationship with perceived well-being and the majority of heart rate variability (HRV) parameters. In contrast, among athletes, increased training load was associated with greater fatigue and reduced overall well-being, without significant correlation with HRV parameters. This may suggest the onset of subjective overfatigue as an early stage of overtraining, particularly in athletes with the highest training volumes.